Pendekatan Interdisipliner dalam Studi Hukum Islam Perspektif M. Atho Mudzhar - Ngainun Naim; Qomarul Huda (Al-Istinbath: Jurnal Hukum Islam, 2021)
Islamic law studies are having a complex dynamic. One of the complexity aspects is related to Islamic law which is increasingly dynamic and has a comprehensive scope. It takes an approach that not only monodisciplinary or multidisciplinary but also interdisciplinary to providing solutions to issues. This article uses a literature review and content analysis, seeks to explain the significance and application of interdisciplinary approaches in Islamic law studies. Based on the sociological Islamic law approaches of M. Atho Mudzhar which delivers insights on exceptionality of Islamic law issues and serve a contribution of Indonesian scholar to the triumph of Islamic studies. This article argues that interdisciplinary approaches made a significant academic contribution to Islamic law studies. Its approach is better than the monodisciplinary in the context of answering contemporary issues.